A four-week training program with the Nordic hamstring exercise during preseason increases eccentric strength of male soccer players - Oliveira, N. T.; Medeiros, T. M.; Vianna, K. B.; Oliveira, G. D. S.; Ribeiro-Alvares, J. B. D. A.; Baroni, B. M. (International Journal of Sports Physical Therapy, 2020)
The Nordic hamstring exercise (NHE) is an effective strategy to prevent hamstring strain injuries in soccer players. The current literature recommends a 10-week training program with three sessions per week, but the short preseason period and the congested schedule make difficult for high-performance soccer teams to apply the NHE as recommended. The purpose of this study was to examine the effect of a pragmatic NHE training program during a four-week preseason period on eccentric knee flexor strength of high-performance soccer players. This study included 25 under-20 male soccer players from a premier league club. They performed eight sessions of NHE (3 sets of 6-10 repetitions, twice a week) during the four-week preseason period. The eccentric knee flexor strength was evaluated during the NHE execution on a custom-made device, before and after the training program. The NHE training program significantly increased the players` eccentric knee flexor strength in both right (Delta=13%; p<0.001; effect size=0.97) and left limbs (Delta=13%; p<0.001; effect size=0.92). Individual analysis identified 76% of the players as responders to the NHE training program (Delta=16%; effect size=1.60), and 24% as non-responders (Delta=3%; effect size=0.24). A four-week training program with NHE performed twice a week is feasible in the real-world of high-performance soccer clubs and increases the eccentric knee flexor strength of male soccer players.